Did it all start with a snowball fight? : and other questions about the American Revolution - Carson, Mary Kay (Good question!, 2012)
"Could a snowball fight really have sparked the American Revolution? What made people get so steaming mad over the price of tea? And did it take a minuteman only a minute to join the fight? Step back into colonial America to find out about taxation without representation; why the British were called lobsters, the first-ever combat submarine and whether Yankee doodles were really dandy!"--